PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS CANVA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Ria Puspita Sari Ria; Muhammad Sofwan; Desy Rosmalinda (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to see the effect of using Canva-based animated video learning media on the learning motivation of class V students at SDN 55/I Sridadi for the 2023/2024 academic year in Pancasila education subjects. This research was conducted in class V of SDN 55/I Sridadi in the 2023/2024 academic year. This research is a quantitative research with a research design using a nonequivalent control group design. The data collection method in this research was observation and questionnaires. Data collection techniques were obtained by filling in observation sheets and giving questionnaires in the form of statements to students. Based on the research results, it shows that the use of Canva-based animated video learning media in the experimental class at SDN 55/I Sridadi has an effect on students' learning motivation. Judging from the average final observation value after giving treatment, it is 38.57, meaning it is more than the average initial observation value before giving treatment, namely 30.81 compared to the control class. Initial observations found an average of 33.24 and a slight increase in observation. The final result is an average of 33.95 with the application of a conventional model that does not use certain treatments. The results obtained from the analysis of the significance value from the Coeficient table were 0.000 < 0.05, so it can be concluded that variable X has an effect on variable Y.